In vitro functionality and endurance of GMP-compliant point-of-care BCMA.CAR-T cells at different timepoints of cryopreservation - Jiang, Genqiao; Neuber, Brigitte; Hückelhoven-Krauss, Angela; Höpken, Uta; Ding, Yuntian; Sedloev, David; Wang, Lei; Reichman, Avinoam; Eberhardt, Franziska; Wermke, Martin; Rehm, Armin; Müller-Tidow, Carsten; et al. (International journal of molecular sciences, 2024)
The search for target antigens for CAR-T cell therapy against multiple myeloma defined the B-cell maturation antigen (BCMA) as an interesting candidate. Several studies with BCMA-directed CAR-T cell therapy showed promising results. Second-generation point-of-care BCMA.CAR-T cells were manufactured to be of a GMP (good manufacturing practice) standard using the CliniMACS Prodigy® device. Cytokine release in BCMA.CAR-T cells after stimulation with BCMA positive versus negative myeloma cell lines, U266/HL60, was assessed via intracellular staining and flow cytometry. The short-term cytotoxic potency of CAR-T cells was evaluated by chromium-51 release, while the long-term potency used co-culture (3 days/round) at effector/target cell ratios of 1:1 and 1:4. To evaluate the activation and exhaustion of CAR-T cells, exhaustion markers were assessed via flow cytometry. Stability was tested through a comparison of these evaluations at different timepoints: d0 as well as d + 14, d + 90 and d + 365 of cryopreservation. As results, (1) Killing efficiency of U266 cells correlated with the dose of CAR-T cells in a classical 4 h chromium-release assay. There was no significant difference after cryopreservation on different timepoints. (2) In terms of endurance of BCMA.CAR-T cell function, BCMA.CAR-T cells kept their ability to kill all tumor cells over six rounds of co-culture. (3) BCMA.CAR-T cells released high amounts of cytokines upon stimulation with tumor cells. There was no significant difference in cytokine release after cryopreservation. According to the results, BCMA.CAR-T cells manufactured under GMP conditions exerted robust and specific killing of target tumor cells with a high release of cytokines. Even after 1 year of cryopreservation, cytotoxic functions were maintained at the same level. This gives clinicians sufficient time to adjust the timepoint of BCMA.CAR-T cell application to the patient’s course of the underlying disease.